Natural Amelioration of Chocolate-Induced Acidity: The Role of Pineapple in Maintaining Oral pH Balance - Haria Fitri; Puji Kurnia; Nila Kasuma; Firahmi Elga (HM Publisher, 2024)
The consumption of chocolate, especially varieties high in sugar, can disrupt the delicate pH balance in the oral cavity, increasing the risk of dental caries. Pineapple, with its rich enzymatic and organic acid profile, presents a potential natural solution to counteract this acidic challenge. This study investigates the efficacy of pineapple consumption in mitigating the pH-lowering effects of chocolate and its impact on saliva volume, a crucial factor in maintaining oral health. A quasi-experimental design with a pre-test and post-test control group approach was employed. Participants included children aged 6-9 years (n=40), divided into two groups: a control group (chocolate consumption only) and an intervention group (chocolate consumption followed by pineapple consumption). Saliva volume and pH were measured before and after treatment, and the data were analyzed using paired t-tests. Pineapple consumption significantly increased saliva volume in the intervention group (from 2.01±1.29 mL to 5.3±0.88 mL, p<0.05), exceeding the volume observed in the control group. Furthermore, the decrease in saliva pH in the intervention group (from 7.45±0.13 to 6.25±0.37) was more controlled compared to the control group (from 7.30±0.09 to 5.28±0.25). In conclusion, the consumption of pineapple after chocolate effectively stimulates saliva production and helps maintain a balanced oral pH, mitigating the acidic effects of chocolate and potentially reducing the risk of dental caries. These findings suggest the potential of pineapple as a natural, dietary approach to support oral health.